Bentuk dan Arti Relasi Makna Sinonim dan Antonim pada Lirik Lagu Album Bernadya (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to describe the forms and meanings of synonymy and antonymy found in the lyrics of the album Bernadya by Bernadya Ribka Jayakusuma using a semantic approach. The study employs a descriptive qualitative method. The data analyzed include words, phrases, and sentences in the song lyrics that contain synonymy and antonymy relations within the album. The data source consists of the lyrics from Bernadya's album. Data collection techniques involve reading, observing, and note-taking methods. Meanwhile, data processing is conducted qualitatively using a hermeneutic approach, which includes the stages of reading, note-taking, and drawing conclusions. Based on the analysis, it was found that the lyrics of Bernadya's album contain two types of semantic relations: synonymy and antonymy.